Modification of SHA-512 using Bcrypt and salt for secure email hashing - Sean Eljim S. Castelo; Ruben Jolo L. Apostol IV; Dan Michael A. Cortez; Raymund M. Dioses; Mark Christopher R. Blanco; Vivien A. Agustin (Indonesian Journal of Electrical Engineering and Computer Science, 2024)
Email security, particularly against phishing, spoofing, and distributed denial-of-service (DoS) attacks, is a pressing concern given the essential role email plays in accessing various online accounts. The study introduced a modified SHA-512 algorithm, implementing additional security layers including randomly generated salt and the Bcrypt algorithm. The modified SHA-512 was comprehensively evaluated on parameters like hash construction, computational efficiency, data integrity, collision resistance, and attack resistance. The results showed its avalanche percentage exceeded the 50% target, reaching 50.08%. Experimental hash-cracking failed to decode the hashes created by the modified algorithm, verifying its protective efficiency. The algorithm also successfully demonstrated data integrity and collision resistance. This indicates that the enhanced SHA-512 algorithm is an effective, more secure hashing method, particularly applicable to email addresses.